2011
DOI: 10.1186/1471-2318-11-42
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating ADL-IADL scales to improve measurement accuracy and to extend the disability construct into the preclinical range: a systematic review

Abstract: BackgroundInterest in measuring functional status among nondisabled older adults has increased in recent years. This is, in part, due to the notion that adults identified as 'high risk' for functional decline portray a state that is potentially easier to reverse than overt disability. Assessing relatively healthy older adults with traditional self-report measures (activities of daily living) has proven difficult because these instruments were initially developed for institutionalised older adults. Perhaps less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 75 publications
(133 reference statements)
1
51
0
1
Order By: Relevance
“…We are aware of some recent calls for improvement for construct validities of the conventional measurements of the ADL and IADL disability scales due to their ceiling effects (i.e., many people reported no disability in these two scales) (Fieo et al 2011). We also notice that the United Nations (Washington City Group 2009) has recently developed a new measure called the Washington City Group general disability measure.…”
Section: Harmonization Of Disability Measurements and Data Collectionmentioning
confidence: 96%
“…We are aware of some recent calls for improvement for construct validities of the conventional measurements of the ADL and IADL disability scales due to their ceiling effects (i.e., many people reported no disability in these two scales) (Fieo et al 2011). We also notice that the United Nations (Washington City Group 2009) has recently developed a new measure called the Washington City Group general disability measure.…”
Section: Harmonization Of Disability Measurements and Data Collectionmentioning
confidence: 96%
“…It has been shown that combining IADL and ADL into a single scale enlarges the coverage of daily functioning measurement [27, 29], yet in the present study, only IADL limitations and participation restrictions provided good fit to unidimensionality. Moreover, as the scale was developed for dementia diagnosis, only dressing and bathing limitations have been evaluated, since they constitute the entry into severe dependency [30].…”
Section: Discussionmentioning
confidence: 57%
“…When instruments show gaps between the least difficult variables, it becomes more difficult to separate between the least disabled individuals; conversely, gaps between the most difficult variables make it more difficult to distinguish between the most disabled persons. [14,30,54] This scenario may be related to both the number and the types of variables included. [14] For both groups of elderly, we found relatively large gaps at both ends of the physical disability measures.…”
Section: Discussionmentioning
confidence: 99%
“…There are no clear guidelines for the recommended size of the gaps between items, although some reports have suggested values between 0.15 and 0.30. [30,47,48] The analyses were performed with SPSS version 21. IBM Corp. Armonk, NY.…”
Section: Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation